Synthesis, Cytotoxicity, and Antileishmanial Activity of N,N'-Disubstituted Ethylenediamine and Imidazolidine Derivatives - Gustavo S. G. de Carvalho; Patrícia A. Machado; Daniela T. S. de Paula; Elaine S. Coimbra; Adilson D. da Silva (The Scientific World Journal)
This paper describes the preparation of N,N'-disubstituted ethylenediamine and imidazolidine derivatives and their in vitro biological activities against Leishmania species. Of the nine synthesized compounds, five displayed a good activity in both L. amazonensis and L. major promastigotes. The compounds 1,2-Bis(p-methoxybenzyl)ethylenediamine (4) and 1,3-Bis(p-methoxybenzyl)imidazolidines (5) showed the best activity on intracellular amastigotes, with IC50 values of 2.0 and 9.4 μ/mL, respectively. In addition, none of compounds were cytotoxic against mammalian cells. The leishmanicidal activity can be related with inhibition of polyamine synthesis and cellular penetration within biological membranes.